Critical slowing down in random anisotropy magnets - Dudka, M.; Folk, R.; Holovatch, Yu.; Moser, G. (Condensed Matter Physics, 2005)
We study the purely relaxational critical dynamics with non-conserved order
parameter (model A critical dynamics) for three-dimensional magnets
with disorder in a form of the random anisotropy axis. For the random axis
anisotropic distribution, the static asymptotic critical behaviour coincides
with that of random site Ising systems. Therefore the asymptotic critical dynamics
is governed by the dynamical exponent of the random Ising model.
However, the disorder effects considerably the dynamical behaviour in
the non-asymptotic regime. We perform a field-theoretical renormalization
group analysis within the minimal subtraction scheme in two-loop approximation
to investigate asymptotic and effective critical dynamics of random
anisotropy systems. The results demonstrate the non-monotonic behaviour
of the dynamical effective critical exponent zeff . Ми вивчаємо релаксаційну динаміку з незбережним параметром
порядку (критична динаміка моделі А) для тривимірного магнетика
з безладом у формі випадкової осі анізотропії. Для анізотропного
розподілу випадкових осей асимптотична критична поведінка співпадає з поведінкою ізингівських систем з випадковими вузлами.
Таким чином асимптотична критична динаміка керується динамічним показником випадкової моделі Ізинга. Однак безлад значно
впливає на динамічну поведінку в неасимптотичному режимі. Ми
проводимо теоретико-польовий ренормалізаційно-груповий аналіз
в рамках схеми мінімального віднімання в двопетлевому наближенні
щоб дослідити асимптотичну і ефективну критичну динаміку систем
з випадковою анізотропією. Результати демонструють немонотонну
поведінку динамічного ефективного критичного показника zeff .